2021
DOI: 10.17507/jltr.1202.02
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Educators’ Conceptions of Language Assessment Literacy in Norway

Abstract: In order to gain a deeper understanding of what language assessment literacy (LAL) is and how it can be developed, it is relevant to investigate it from the point of view of different stakeholders (Harding & Kremmel, 2016). As for teacher LAL, this phenomenon has largely been studied from the teachers’ own perspectives, leaving other stakeholders’ understanding of the construct underresearched. The current study used an exploratory, qualitative research design to investigate teacher educators’ conceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…There has been an increasing interest in LAL among researchers and practitioners over the last decades (Davies, 2008;Fulcher, 2010Fulcher, , 2012Malone, 2013) which has led to a large body of research across different settings (Bøhn & Tsagari, 2021;Coombe et al, 2012;Homayounzadeh & Razmjoo, 2021;Janatifar & Marandi, 2018;Popham, 2009;Shahzamani & Tahririan, 2021;Stiggins, 1995;Vogt & Tsagari, 2014;Wang et al, 2006;Watmani et al, 2020;Xu & Brown, 2016;Yan & Fan, 2021;Zhou et al, 2020). Due to space limit, only some are reviewed to lay the groundwork for the current study.…”
Section: Research On Teachers' Perceptions Of Lalmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increasing interest in LAL among researchers and practitioners over the last decades (Davies, 2008;Fulcher, 2010Fulcher, , 2012Malone, 2013) which has led to a large body of research across different settings (Bøhn & Tsagari, 2021;Coombe et al, 2012;Homayounzadeh & Razmjoo, 2021;Janatifar & Marandi, 2018;Popham, 2009;Shahzamani & Tahririan, 2021;Stiggins, 1995;Vogt & Tsagari, 2014;Wang et al, 2006;Watmani et al, 2020;Xu & Brown, 2016;Yan & Fan, 2021;Zhou et al, 2020). Due to space limit, only some are reviewed to lay the groundwork for the current study.…”
Section: Research On Teachers' Perceptions Of Lalmentioning
confidence: 99%
“…The findings revealed that although most of the participants had required assessment literacy, some could not even make a distinction between "assessment of learning" and "assessment for learning." Exploring teacher educators' understandings of LAL in Norway was the focus of a study carried out by Bøhn and Tsagari (2021), indicating that for the participants, LAL includes four primary competences, namely disciplinary, assessment-specific, pedagogical, and collaboration. More recently, Yan and Fan (2021) conducted a qualitative study to explore the contextual and experiential factors affecting language testers, EFL teachers, and graduate students' LAL profile in the Chinese context.…”
Section: Research On Teachers' Perceptions Of Lalmentioning
confidence: 99%
“…Giraldo ( 2018) is my most cited, and it has been used to highlight trends in the field (Bøhn & Tsagari, 2021;Butler, Peng, & Lee, 2021), differentiate LAL from its generic term, assessment literacy (Lan & Fan, 2019;Sultana, 2019), and discuss LAL against teachers' professional development and practice (Buendía & Macías, 2019;Rauf & McCallum, 2020). The citations come from researchers both in Colombia and elsewhere.…”
Section: What Is Language Assessment Literacy (Lal)?mentioning
confidence: 99%
“…The collaboration helped the course instructor enhance her LAL as well. While course instructors are influential stakeholders in teacher education, less information about their LAL is known (Bøhn and Tsagari 2021;Jeong 2013). In the current study, the authors confirmed that through interaction with the inservice teacher, the course instructor also developed further understanding of the ways to contextualize language assessment theories and practices.…”
Section: The Course Instructor's Lal Enhancementmentioning
confidence: 99%